Profil Kemampuan Pemecahan Masalah Siswa SMP pada Materi Bangun Datar Segiempat - Nurul Fitria Hapsari Raharjo (Universitas Muria Kudus, 2022)
This research started from the problems that occurred in several junior high school/MTs level schools in Karawang with the students' mathematical problem solving ability which was still low. This research is a qualitative research that aims to describe students' mathematical problem solving abilities which are analyzed based on Polya's completion steps, which include: understanding the problem, planning a settlement strategy, executing a settlement strategy and checking the results. Test and non-test instruments were used in this study. The test instrument was in the form of a story about the subject matter of Quadrilateral and a non-test instrument in the form of an interview. Sampling in this study was carried out by purposive sampling, the class selected as the research sample was class VII-A with a sample of 3 students in the category of high, medium and low ability students based on the selection of class teachers. The results showed that students' mathematical problem solving abilities were diverse. In general, students in the high category have good mathematical problem solving abilities. However, it was also found that high-ability students sometimes erred in operating algebraic forms. One of the factors of errors made by students is because students are not accustomed to answering questions of problem solving types.